I'm a poor lonesome rider. Help! I could dope. Issue 2 (August 2018) - Fincoeur, Bertrand; Cunningham, Rachel; Ohl, Fabien
Abstract: There is some evidence that the widespread culture of tolerance towards doping within elite cycling has been splintered over the past two decades. Not unsurprisingly when looking back at cycling's recent history, elite teams are now expected to take an active part in doping prevention. In particular, we show in this article that weak team supervision and precarious work conditions may impact individual doping risks. Based on these two indicators, we then develop four ideal types of dopers. Finally, we elaborate on policy implications for doping prevention. This article is based on aggregated results from two research projects on doping in elite cycling. In total, 109 interviews were conducted with elite riders and staff members from eleven elite teams, as well as other stakeholders.